Writing Spaces Readings on Writing Vol. I - Lowe, Charlie; Zemliansky, Pavel (Open textbook library., 2010)
Volumes in Writing Spaces: Readings on Writing offer multiple perspectives on a wide-range of topics about writing, much like the modelmade famous by Wendy Bishop's “The Subject Is . . .” series. In eachchapter, authors present their unique views, insights, and strategies forwriting by addressing the undergraduate reader directly. Drawing ontheir own experiences, these teachers-as-writers invite students to joinin the larger conversation about developing nearly every aspect of thecraft of writing. Consequently, each essay functions as a standalonetext that can easily complement other selected readings in writing orwriting-intensive courses across the disciplines at any level. Topics in Volume 1 of the series include academic writing, how to interpret writing assignments, motives for writing, rhetorical analysis, revision, invention, writing centers, argumentation, narrative, reflective writing, Wikipedia, patchwriting, collaboration, and genres.